Belief in misinformation and acceptance of COVID-19 vaccine boosters: A survey analysis - Stephen R. Neely; Kaila Witkowski (Elsevier, 2024)
Objective: This study examines the impact of misinformation belief on the willingness of American adults to receive ongoing COVID-19 vaccine boosters. Methods: A representative survey of 600 adults in the state of Florida was fielded in August of 2023. For this study, responses were analyzed for the 443 previously vaccinated respondents in that sample using both descriptive and inferential statistical methods. Results: Among previously vaccinated individuals, belief in misinformation remained relatively high. 49% of respondents believe that COVID-19 vaccines contain a live strain of the virus, and roughly 40% believe that vaccines can cause you to "get sick" with COVID-19. Belief in misinformation was associated with a statistically significant decrease in the likelihood of receiving ongoing vaccine boosters, ceteris paribus. Conclusion: While confidence in public health guidelines is the most compelling determinant of vaccine acceptance, misinformation continues to undermine vaccination efforts. Addressing common myths about COVID-19 vaccines may help to improve booster shot acceptance among previously vaccinated Americans. Innovation: Throughout the COVID-19 pandemic, health professionals and public health agencies have been forced to innovate in real-time, as digital platforms have fueled the spread of viral misinformation. This study aims to inform these efforts by exploring and deepening our understanding of the impact that belief in misinformation has on vaccination behaviors.